Taking into account size factor when selecting a land plot for multi-family housing construction - LIZUNOVA, Alina; LYTVYNENKO, Iryna (Ways to Improve Construction Efficiency, 2025)
The article analyzes the factor of land plot size (S) considered in the SWAP analysis when selecting a land plot for multi-apartment construction. It has been established that size goes beyond simple area, functioning as a comprehensive regulatory tool that balances the economic feasibility of a project and the social justice of urban land use. The inseparable connection between the land plot size factor and the normative building density is investigated. This factor, in combination with the number of floors, determines the maximum permissible volume of construction, which allows controlling the load on engineering and social networks, preventing overpopulation. It is shown that the required area of residential territories is clearly differentiated depending on the number of storeys of housing (the need for horizontal space increases from high-rise to detached housing). These consolidated standards already integrate all functional elements: housing, services, landscaping, transport network and utilities. The maximum parameters for development have been determined: an inverse relationship has been established, where the percentage of development of a plot is strictly limited and decreases with the increase in the number of floors. The total area under development also has a strict limit, which applies provided that adequate access roads and engineering protection are ensured. Particular attention is paid to spatial and sanitary requirements: The specific area per resident is strictly limited by the number of floors. Insolation (domestic) gaps between buildings and setbacks from red lines must ensure the necessary lighting and safety. Transport infrastructure (requirements for the width of passageways, the availability of turning areas) and parking standards, which depend on the functional zoning of the city, are regulated. The use of adjacent territories for functional areas (games, recreation, sports) and sanitary zones (waste collection, walking animals) is detailed, with mandatory compliance with insulation gaps.